2017
DOI: 10.1075/gest.16.2.06edw
|View full text |Cite
|
Sign up to set email alerts
|

Sign-creation in the Seattle DeafBlind community

Abstract: This article examines the social and interactional foundations of sign-creation among DeafBlind people in Seattle, Washington. Linguists studying signed languages have proposed models of sign-creation that involve the selection of an iconic gestural representation of the referent which is subjected to grammatical constraints and is thereby incorporated into the linguistic system. Drawing on 18 months of ethnographic fieldwork and more than 190 hours of video recordings of interaction and language use, I argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…Channels are caught up in these reroutings, but the protactile movement didn't start there. In the beginning, DeafBlind people intervened in conventions that were widespread at the time in order to re‐consider their environment—not their language (Edwards ). They were not thinking: how can I get this linguistic sign from me to you— they were thinking more broadly about what it would mean to be in the world together and what that world might have to offer.…”
Section: Channelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Channels are caught up in these reroutings, but the protactile movement didn't start there. In the beginning, DeafBlind people intervened in conventions that were widespread at the time in order to re‐consider their environment—not their language (Edwards ). They were not thinking: how can I get this linguistic sign from me to you— they were thinking more broadly about what it would mean to be in the world together and what that world might have to offer.…”
Section: Channelsmentioning
confidence: 99%
“…If this is the case, then infrastructure surely plays a role in shaping, reinforcing, and responding to those patterns. In prior research, I have shown how new articulatory and perceptual affordances revealed themselves to DeafBlind people in Seattle when new participant frameworks and patterns in interaction began to emerge (Edwards , ). This research suggests that additional pressures are exerted on those channels of transmission by larger infrastructural dynamics.…”
Section: Architecture Infrastructure and Participationmentioning
confidence: 99%
See 3 more Smart Citations